Global Dynamics and Emerging Spaces : Expert Power, Policy Assemblages, and Evidence-Based Policymaking in Nordic Education Reforms - Volmari, Saija (Helsingin yliopisto, 2024)
This dissertation focuses on the use of evidence and expertise in the recent school reforms in the Nordic countries, and the co-creation of global policy space and national policy contexts through the social interactions and networks of knowledge and experts. The study positions itself at the intersection of several disciplines, including education, sociology, geography, and political sciences. Drawing inspiration from previous research in education policy transfer, globalization studies, spatiotemporal theories, and assemblage thinking, this research sheds light on the interwoven and assemblage nature of the national, Nordic, and international policy contexts. The data used in this dissertation stems from the extensive research conducted in the Policy Knowledge and Lesson Drawing in Nordic School Reform (POLNET) project. It was produced in 2019–2021. Financed by the Norwegian Research Council and led by the University of Oslo, this collaborative effort engaged researchers from six universities in the Nordic countries and the US. Through the meticulous collection and coding of bibliometric references from key policy documents in recent Nordic school reforms, POLNET presents a robust dataset comprising 5391 references. This dissertation focuses on specific subsets of this data: the Finnish database of bibliometric references (N=677), Nordic references across all five cases of Nordic countries (N=255), ten pivotal policy documents from the Finnish reform, and 18 semi-structured expert interviews conducted in Finland (N=5), Iceland (N=5), and Norway (N=8). A novel approach to data analysis is employed to trace moments when the global dimension surfaces within the national context. It explores instances where, in processes of globalization, global evidence produced especially by the international organizations influences national policy formation or where national actors engage in shaping global policy within the realms of national, regional, and global policy creation spaces. The dissertation is structured into ...